Study of role of amniotic fluid total protein (AFTP) assessment in the diagnosis of tubercular ascites - Kalmegh, Rohan; Chaudhary, Sameer (International Journal of Advances in Medicine, 2018)
Background: It is not economically feasible to estimate the serum and ascitic albumin level for calculating Serum Ascites Albumin Gradient (SAAG) in every suspected tubercular ascites patient. Ascites fluid total protein (AFTP) seems a cheaper and viable alternative. Authors attempted to compare the efficacy of Amniotic Fluid Total Protein (AFTP) against Serum Ascites Albumin Gradient (SAAG) in the diagnosis of Tubercular Ascites. Methods: Patients who were admitted to Medicine Wards, with the complaints of distension of abdomen, proved by ultrasound to have ascites, were included in the study. Total 102 Patients of ascites were included. The incidence of Tuberculous ascites was observed and special features regarding their clinical presentation, ascitic fluid values and imaging studies were noted. Results: Tubercular ascites was seen in 18 (17.6%) patients out of the 102 subjects studied. In the group of patients having raised ascitic fluid ADA, authors found that the number of patients having raised AFTP (16 cases, 88.88%) was significantly more than the patients having lower SAAG (13 cases, 71.22%) (p=0.007). Conclusions: In the setting where calculating SAAG may prove to be quite expensive, AFTP is a reasonable predictor of Tubercular infection in ascitic fluid.